2010
DOI: 10.1016/j.ajhg.2010.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Mutations in HPSE2 Cause the Autosomal Recessive Urofacial Syndrome

Abstract: Previously, we localized the defective gene for the urofacial syndrome (UFS) to a region on chromosome 10q24 by homozygosity mapping. We now report evidence that Heparanse 2 (HPSE2) is the culprit gene for the syndrome. Mutations with a loss of function in the Heparanase 2 (HPSE2) gene were identified in all UFS patients originating from Colombia, the United States, and France. HPSE2 encodes a 592 aa protein that contains a domain showing sequence homology to the glycosyl hydrolase motif in the heparanase (HPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 21 publications
0
52
1
3
Order By: Relevance
“…Homozygosity-mapping, on the other hand, is a more powerful and effective approach to study recessive disorders in consanguineous families (Harville et al 2010;Pang et al 2010;Iseri et al 2010;Collin et al 2010). For those disorders that are not amendable to these two conventional approaches, their causal variants remain elusive.…”
Section: Introductionmentioning
confidence: 97%
“…Homozygosity-mapping, on the other hand, is a more powerful and effective approach to study recessive disorders in consanguineous families (Harville et al 2010;Pang et al 2010;Iseri et al 2010;Collin et al 2010). For those disorders that are not amendable to these two conventional approaches, their causal variants remain elusive.…”
Section: Introductionmentioning
confidence: 97%
“…This approach has been shown to be powerful and is particularly useful in investigating autosomal recessive disorders especially in populations with a high prevalence of consanguinity. This is evident from the enormous number of studies identifying causal mutations for autosomal recessive disorders in consanguineous families (Abu SaWeh et al 2010;Harville et al 2010;Walsh et al 2010;Pang et al 2010;Lapunzina et al 2010;Nicolas et al 2010;Uz et al 2010;Iseri et al 2010;Collin et al 2010). However, the Wrst study applying the homozygosity association approach at the genome-wide scale for complex diseases only appeared in 2007 (Lencz et al 2007).…”
Section: Implications On Complex Diseases and Traitsmentioning
confidence: 94%
“…However, UFS-causing gene mutations were first reported by two groups in 2010 [13,14]. To date, 10 different HPSE2 gene mutations have been reported in a total of 28 UFS patients from 17 families in different studies [13,14,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that HPSE2 and LRIG2 mutations have not been detected in all patients. Pang et al [14] evaluated nine families with UFS and have detected HPSE2 mutations in all families. However, Daly et al [13] found HPSE2 mutations in six (60%) of 10 families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation